One-Sun CPC-type solar collectors with evacuated tubular receivers. (April 2019) - Osório, T.; Horta, P.; Marchã, J.; Collares-Pereira, M.
Abstract: The collection of solar energy in the upper part (80–150 °C) of the low temperature range commonly relies on evacuated tubular collectors with or without a back reflector. The reflector is usually of the CPC type and designed for a collector concentration ratio below 1. Increasing the concentration ratio lowers thermal loss while limiting the collector acceptance angle. A hemispherical acceptance makes the installation fully flexible, i.e. the collectors can be installed on surfaces with any tilt, and both in North-South or East-West tube orientations. If a hemispheric acceptance is intended, the theoretical upper limit of the concentration ratio is exactly 1. We investigated near-one-concentration (One-Sun) CPC-type solar collectors with different virtual absorber geometries for the same evacuated tubular receiver to identify designs with low materials and manufacturing production costs. We compared four different designs and built a prototype of the most promising one. Experimental tests showed an increase of 79 °C in the receiver stagnation temperature, albeit a poor reflector shape quality. We present some ideas on how to deal with the difficult subject of overheating that would lead to a reduction of up to 36% in the zero-loss efficiency at normal incidence for the selected design. Highlights: Simplified CPC-type reflector designs with 90° acceptance angles. Lower materials and manufacturing costs keeping good optical and thermal performance. Power reduction up to 36% using reflector linear movements for overheating prevention.